The Chinese belt and road initiative between economics and geopolitics: Consequences for Armenia - Ralph Wrobel (OrdnungsPolitisches Portal (OPO), 2022)
Armenia has already signed some agreements with China to participate in the BRI project while no concrete measures are financed by the initiative. But what are the economic advantages and disadvantages of the BRI? While funding of some for Western financiers unattractive projects by China is a good chance for some participating countries a resulting "debt trap" is dangerous for them. Additionally, it can be shown easily that China's investments have mostly some geopolitical aspects which make the projects more advantageous for China than for the participating countries themselves. Especially, when in the BRI participating countries cannot pay back their debts a transfer of natural resources respective of infrastructure like ports ore pipelines to China may be the consequence. Therefore, Armenia is in a dilemma between strengthening cooperation with China and benefitting from that, on the one hand, and the risk of losing economic as well as political independence, on the other hand.
Keywords: 330; Belt and Road Initiative; Armenia; Geopolitics; Debt-Trap